TRANSFORMASI MANAJEMEN PERPUSTAKAAN DI ERA DIGITAL: TANTANGAN DAN PELUANG - Oktavia, Ariska (UIN Imam Bonjol Padang, 2024)
The development of digital technology has brought significant changes to library management, presenting new challenges and opportunities. This article aims to investigate how digital technology affects library management practices and how libraries can adapt to these changes. The research employs a Systematic Literature Review (SLR) approach to analyze relevant literature from 2014 to 2024, focusing on the impact of digital technology on library services, the challenges faced, and the opportunities that can be leveraged. The findings indicate that libraries face various challenges, including limited resources, staff resistance to new technologies, and information security issues. Nevertheless, digital technology also offers opportunities to enhance operational efficiency through automation, better data management, and the development of interactive services that can increase user engagement. The research reveals that the integration of artificial intelligence (AI) and data analytics can assist libraries in making better decisions and improving user experiences. The conclusion of this research emphasizes the importance of library management in formulating policies that support adaptation to new technologies and creating an organizational culture that is open to change. By effectively leveraging digital technology, libraries can strengthen their position as knowledge centers in society and meet the evolving information needs of users. Strategic recommendations are suggested to enhance librarian training and establish collaborative partnerships to address challenges and capitalize on opportunities in the digital era.